Refleksi Mahkamah Konstitusi Sebagai The Guardian Of Constitution: Tantangan Dan Permasalahan Dalam Rangka Mewujudkan Kekuasaan Kehakiman Yang Merdeka - Endang Wahyuni Setyawati; Eva Kurnia Mochtar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The Constitutional Court (MK), as a state institution exercising judicial power, plays a vital role in upholding constitutional supremacy and reinforcing the principles of a rule of law. However, in carrying out its duties and authorities, the Court faces various challenges and issues that may affect its effectiveness and independence. Therefore, this study aims to reflect on the role of the Constitutional Court as the guardian of the constitution in the context of realizing an independent judiciary as mandated by the 1945 Constitution. This research adopts a normative juridical approach by analyzing the development of regulations, state practices, and relevant Constitutional Court decisions. Several key challenges and issues identified include: the term of office of constitutional justices, the issue of centralized judicial review authority, the absence of external oversight for constitutional justices, and the financial independence of the judiciary